Lacunar syndromes due to brainstem infarct and haemorrhage. - Huang, C (1988)
Nine patients with brainstem infarct and two with brainstem haemorrhage presented with pure motor stroke, pure supranuclear facial palsy, sensorimotor stroke or ataxic hemiparesis. Despite the clinical similarity with hemispheric lacunes, brainstem infarcts causing lacunar syndromes probably have a greater tendency to progress. Small brainstem haemorrhages should also be considered as a cause of lacunar syndromes and the difficulty in differentiating them from small infarcts without CT is emphasised.